Mobile AR Requirements for Location Based Social Networks - Turunen, Tuukka; Pyssysalo, Tino; Röning, Juha (International Journal of Virtual Reality, 2010)
Utilizing the novel User Interface (UI) technology of Augmented Reality (AR) in mobile phones provides significant advantages for Location Based Social Networks (LBSN) via powerful UI that allows the user to see the world through AR view rather than via a traditional map view. Compared to use of a map based interface, it is much easier for the user to understand where the nearby friends and points of interests are located when using a mobile AR interface to access the information of LBSN services. Recent development in the commercially available high end mobile phones has made it a viable device to use globally available AR services, but there still exist some limitations when it comes to LBSN services. Especially demanding is the need to include constantly moving friends reliably and accurately as annotated objects into the AR view of a user. In this article we show for the first time that mobile phones can be utilized to create mobile AR based LBSN services and create an experimental system to validate this. We present the most important use cases of the mobile AR based LBSN services, define the key requirements for the system, and analyze how the current high end mobile phones meet these. We point out the main challenges in position and orientation accuracy, data transfer and power consumption, as well as solutions to improve these. We present results from end-user studies and our experimental system we have created to study mobile AR interface for the LBSN services, and conclude that the mobile phones can be used for creation of these services when the key challenges are resolved